Genetic screening of 202 individuals with congenital limb malformations and requiring reconstructive surgery - Furniss, D; Kan, S-h; Taylor, I B; Johnson, D; Critchley, P S; Giele, H P; Wilkie, A O M (Journal of medical genetics, 2009)
Background:Congenital limb malformations (CLMs) are common and present to a variety of specialties, notably plastic and orthopaedic surgeons, and clinical geneticists. The authors aimed to characterise causative mutations in an unselected cohort of patients with CLMs requiring reconstructive surgery.Methods:202 patients presenting with CLM were recruited. The authors obtained G-banded karyotypes and screened EN1, GLI3, HAND2, HOXD13, ROR2, SALL1, SALL4, ZRS of SHH, SPRY4, TBX5, TWIST1 and WNT7A for point mutations using denaturing high performance liquid chromatography (DHPLC) and direct sequencing. Multiplex ligation dependent probe amplification (MLPA) kits were developed and used to measure copy number in GLI3, HOXD13, ROR2, SALL1, SALL4, TBX5 and the ZRS of SHH.Results:Within the cohort, causative genetic alterations were identified in 23 patients (11%): mutations in GLI3 (n = 5), HOXD13 (n = 5), the ZRS of SHH (n = 4), and chromosome abnormalities (n = 4) were the most common lesions found. Clinical features that predicted the discovery of a genetic cause included a bilateral malformation, positive family history, and having increasing numbers of limbs affected (all p<0.01). Additionally, specific patterns of malformation predicted mutations in specific genes.Conclusions:Based on higher mutation prevalence the authors propose that GLI3, HOXD13 and the ZRS of SHH should be prioritised for introduction into molecular genetic testing programmes for CLM. The authors have developed simple criteria that can refine the selection of patients by surgeons for referral to clinical geneticists. The cohort also represents an excellent resource to test for mutations in novel candidate genes.